MATERNAL MORBIDITY IN EMERGENCY VERSUS ELECTIVE CAESAREAN SECTION AT TERTIARY CARE HOSPITAL - Ghazi, Asifa; Karim, Farah; Hussain, Ayesha Muhammad; Ali, Tehmina; Jabbar, Shazia (Journal of Ayub Medical College Abbottabad, 2012)
Background: In the past 30 years the rate of caesarean section (C/S) has steadily increased from 5% to more than 20% for many avoidable and unavoidable indications. The objective of this study was to compare maternal morbidity and determine its cause in elective and emergency caesarean section. Method: It was a cross-sectional comparative study conducted in Civil Hospital Karachi at Obs/Gyn Unit III. All mothers admitted through OPD or emergency during the study period, of any age or parity undergoing C/S were recruited in the study. Patients having previous myomectomy, hysterotomy or classical C/S were excluded from the study. Patients undergoing emergency C/S were placed in group A, and those delivered by elective C/S were included in group B. Study variables were general and obstetric parameters and complications observed intra-operatively. Any postoperative complications were recorded from recovery room till patient was discharged from the ward. Results: There were 50 patients in each group. In group A, 11 (22%) were booked and 33 (66%) were referred cases. In group B, 48 (96%) were booked. The mean age in both groups was 28 years. In both groups, multigravida compared to primigravida were 78% vs 22% in group A, and 92% vs 8% in group B. Indication for C/S was previous C/S in 10 (20%) patients in group A, and 39 (78%) patients in group B, placenta previa, chorioamionitis, obstructed labour (6, 12% each); pregnancy induced hypertension and eclampsia in 5 (10%) cases in group A only. Intra-operative complications in group A were 48 (96%) vs 15 (30%) in group B (p=0.000). Postoperative morbidity in group A was 50 (100%) and 26 (52%) in group B (p=0.000). Intra-operative complication was haemorrhage in 46 (92%) cases in group A and 11 (22%) in group B. Anaesthetic complications were 40 (80%); prolonged intubation 25 (50%), aspiration of gastric contents 8 (16%), and difficult intubation 7 (14%) in group A. Ten (20%) cases had anaesthetic complications in group B. Commonest postoperative complication in both groups was anaemia in 41 (82%) and 11 (22%) cases respectively. Conclusion: Maternal morbidity is significantly higher in emergency C/S. Haemorrhage is a frequent complication in C/S, emergency or elective. Keywords: Emergency C/S, Elective C/S, Maternal, Caesarean Section, Morbidity and Mortality